The Tuberculosis Register - An evaluation of its use and impact under epidemic conditions in the Western Cape Province of South Africa. - R.J. Mash; N. Coetzee; S. Patel; A. Heywood (South African Family Practice)
Study objective: To evaluate whether the Tuberculosis Register, as part of the South African National Tuberculosis Control Programme, is achieving its objective of monitoring the programme and decentralising the use of information for planning and action to the facility level. Design: Quantitative and qualitative research methods were used to evaluate the effectiveness of the Tuberculosis Register. The design included self-administered questionnaires and focus group discussions with clinic staff, direct observations of the Register and semi-structured interviews with managers of the Tuberculosis Programme. Setting: A purposefully selected sample of 17 facilities in 7 of the 25 districts in the Western Cape Province of South Africa. Results: The 2-month sputum result was completed in 75% and the discharge sputum result in 67% of Registers, demonstrating poor data collection for the calculation of treatment outcomes. Several categories of data were seldom collected such as the identity number in 25% and adherence in 22% of Registers. Only 43% of facilities calculated the indicators for treatment outcome demonstrating a failure to analyse the data at this level. Only 40% of facilities received written feedback on performance from higher levels. The focus groups found little evidence that information was used for planning or action at the facility level. Conclusions: The Tuberculosis Register has not fulfilled its objectives of improving local planning and management of the Tuberculosis programme through the collation, analysing and interpretation of data at a facility level. A number of recommendations to improve the performance of the Tuberculosis Register are made.